2016
DOI: 10.4103/2211-4122.183761
|View full text |Cite
|
Sign up to set email alerts
|

A unique variation of azygos system of veins

Abstract: Knowledge of variations of azygos and hemiazygos veins is of importance to cardiothoracic surgeons and radiologists during various surgical, radiological, and echography techniques. We report some unique variations of azygos system of veins observed during dissection classes for undergraduate medical students. The azygos vein was formed as usual by the union of right subcostal and ascending lumbar veins. The vein ascended upward and to the left to reach the midline at the level of the 9th thoracic vertebra. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Veins that drain into the Azygos are the right superior intercostal vein, 5 th –11 th right posterior intercostal veins, hemiazygos vein, accessory hemiazygos vein, pericardial, bronchial, and esophageal veins. The Azygos provides collateral venous circulation between the SVC and the IVC with two ways shunt since it has few to no valves [6]. As such, the Azygos vein has a significant clinical role in cases of increased venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Veins that drain into the Azygos are the right superior intercostal vein, 5 th –11 th right posterior intercostal veins, hemiazygos vein, accessory hemiazygos vein, pericardial, bronchial, and esophageal veins. The Azygos provides collateral venous circulation between the SVC and the IVC with two ways shunt since it has few to no valves [6]. As such, the Azygos vein has a significant clinical role in cases of increased venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The accessory hemi-azygos vein is absent and the hemi-azygos vein is present draining into the azygos vein. In 2 male cadavers there were 3 transverse channels connecting the accessory hemiazygos and hemiazygos with the azygos vein [11]. Badagabettu S N, literature survey also revealed a case where the hemiazygos vein was absent with the presence of right and left azygos veins [12].…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Seib (1934) Nayak and Soumya [10] have described a reversed azygos system with the azygos shifted to the left side and draining into the brachiocephalic vein and the accessory and hemiazygos system shifted to the right side of the body. Badagabettu et al [11] have reported a hemiazygos vein with multiple linkages to the azygos vein across the midline. Neither of the cases reported by these authors or others was similar to our case, where two more or less vertical venous chains converged into a single vein inferiorly to drain into the IVC and, just prior to this, formed a circular venous plexus.…”
Section: Anatomical Variationsmentioning
confidence: 99%